Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Yes, if fₙ and gₙ are sequences of Real numbers such that converge uniformly to f and g, on A⊂ R respectively, then (fₙ gₙ) isconverges uniformly to (f g).
Suppose fn → f uniformly and gn → g uniformly
on A ⊆ R and that both f and g are bounded. Then (fₙ.gₙ) converges uniformly to (fg) on A.
Proof. Let ε > 0. Suppose M₁ > 0 is an upper bound for f (meaning |f(x)| ≤ M₁ for all x ∈ A) and that M₂ is an upper bound for g.
Since fn → f uniformly, there exists N₁ ∈ N such
that n ≥ N₁ implies |fn(x) − f(x)| < 1 for all x ∈ A. Equivalently, |fn(x)| < |f(x)| + 1 ≤ M₁ + 1 for all
x ∈ A.
In turn, since gn → g uniformly, there exists N₂ ∈ N such that n ≥ N₂ implies
|gn(x) − g(x)| < 2(M₂ + 1).
Finally, since fn → f uniformly, there exists N₃∈ N such that n ≥ N3 implies |fn(x) − f(x)| < 2M₂ .
Now, if N = max{N₁, N₂, N₃} and n ≥ N, we have
|fn(x)gn(x) − f(x)g(x)| = |fn(x)gn(x) − fn(x)g(x) + fn(x)g(x) − f(x)g(x)|
≤ |fn(x)gn(x) − fn(x)g(x)| + |fn(x)g(x) − f(x)g(x)|
= |fn(x)||gn(x) − g(x)| + |g(x)||fn(x) − f(x)|
≤ (M₁ + 1)|gn(x) − g(x)| + M₂|fn(x) − f(x)|
< (M₁ + 1) ε/2(M₁ + 1) + εM₂/2M₂
= ε for all x ∈ A So, we see that, indeed, (fngn) → (fg) uniformly on A. Hence proved.
To learn more about Uniform convergence of sequence, refer:
https://brainly.com/question/16294413
#SPJ4
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.